1993
DOI: 10.3758/bf03205268
|View full text |Cite
|
Sign up to set email alerts
|

Estimating local shape from shading in the presence of global shading

Abstract: In theory, global shading may help with the estimation of local surface structure from shading (e.g., in specifying the illuminant direction). Empirically, we do not know whether human observers combine the information given by the local and global shading to estimate local shape.Observers had to indicate the orientation of a local elongated perturbation with or without global shading information provided by a background surface. Our psychophysical results show the following:1. Observers do not estimate the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…The results of this research showed clearly that observers' slant judgments for simple planar surfaces tend to be systematically underestimated, and that they can be highly unreliable as well. More recently, similar findings have been obtained for judgments of local metrical structure (e.g., relative depths or orientations) with the use of more complex scenes of smoothly curved surfaces, and for objects depicted with several different types of optical information such as shading (e.g., Erens, Kappers, & Koenderink, 1993;Koenderink, van Doorn, & Kappers, 1992;Mingolla & Todd, 1986), texture (e.g., Todd & Akerstrom, 1987), motion (e.g., Todd &Bressan, 1990;Todd & Norman, 1991), and binocular disparity (e.g., Foley, 1980;McKee, Levi, & Bowne, 1990).…”
supporting
confidence: 66%
“…The results of this research showed clearly that observers' slant judgments for simple planar surfaces tend to be systematically underestimated, and that they can be highly unreliable as well. More recently, similar findings have been obtained for judgments of local metrical structure (e.g., relative depths or orientations) with the use of more complex scenes of smoothly curved surfaces, and for objects depicted with several different types of optical information such as shading (e.g., Erens, Kappers, & Koenderink, 1993;Koenderink, van Doorn, & Kappers, 1992;Mingolla & Todd, 1986), texture (e.g., Todd & Akerstrom, 1987), motion (e.g., Todd &Bressan, 1990;Todd & Norman, 1991), and binocular disparity (e.g., Foley, 1980;McKee, Levi, & Bowne, 1990).…”
supporting
confidence: 66%
“…Studies that used complex illuminated objects with strong lighting direction cues concluded that lighting cues guide shape-from-shading (6, 7), whereas studies that used weaker lighting cues concluded that they have little effect (8)(9)(10)(11)(12). We discuss the lighting cues in previous studies in further detail in SI Discussion.…”
Section: Resultsmentioning
confidence: 99%
“…When variations in local shape are experimentally isolated from global information about the irradiance distribution and surrounding surface structure, local shape is very poorly resolved (Erens, Kappers, & Koenderink, 1993a, 1993b. In the Erens et al (1993b) study, observers' categorical shape judgments (eight regions of the shape index-Eq.…”
Section: Image Shadingmentioning
confidence: 99%